2019
DOI: 10.1093/femsle/fnz187
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting effects of isocitrate dehydrogenase deletion on fluxes through enzymes of central metabolism in Escherichia coli

Abstract: Flux analysis is central to understanding cellular metabolism and successful manipulation of metabolic fluxes in microbial cell-factories. Isocitrate dehydrogenase (ICDH) deletion conferred contrasting effects on fluxes through substrate-level phosphorylation (SLP) reactions. While significantly increasing flux through pyruvate kinase, it diminishes flux through succinyl CoA synthetase and upregulates phosphotransacetylase (PTA) and acetate kinase (AK). In addition to acetate, the ICDH-less strain excretes pyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…It was previously suggested that limited availability of HS‐CoA in a cell could be a constraint for the metabolic flux because HS‐CoA is a common cofactor for PDHc and 2‐oxoglutarate dehydrogenase complex (OGDHc) [24]. Together with this, our previous study showed the requirement of the OGDHc activity for the growth after glucose depletion because knockout mutants of OGDHc subunits showed complete growth arrest after glucose depletion [16].…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…It was previously suggested that limited availability of HS‐CoA in a cell could be a constraint for the metabolic flux because HS‐CoA is a common cofactor for PDHc and 2‐oxoglutarate dehydrogenase complex (OGDHc) [24]. Together with this, our previous study showed the requirement of the OGDHc activity for the growth after glucose depletion because knockout mutants of OGDHc subunits showed complete growth arrest after glucose depletion [16].…”
Section: Resultsmentioning
confidence: 73%
“…It has been known that pyruvate accumulated in the cells is easily excreted into the culture medium [24,41]. Thus, we analyzed the pyruvate accumulation in the medium and it was observed that the pta mutant accumulated extracellular pyruvate after glucose depletion (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation